Android-based diet consultant - Tnek, Shiin Wei (2023)
In a world where health risks related to diet are of growing concern, the Android-based Diet Consultant application emerges as a proactive solution. This application is meticulously crafted to simplify and promote healthy dietary practices and lifestyle choices by comparing the existing implementation in the market as explored in Chapter 2 during the Literature Review. Serving as a virtual dietitian, it empowers users to effortlessly generate personalized diet plans, as detailed in Chapter 4, eliminating the need for traditional in-person consultations. This not only saves valuable time but also allows users to create tailored dietary regimens based on their individual data with unparalleled ease, a process outlined in Chapter 4 as part of the Project Specification. Beyond diet planning, as discussed in Chapter 5 during the Design phase, the application actively monitors and tracks user progress, providing insights and feedback for a holistic health journey. Moreover, the inclusion of an AI diet chatbot, implemented in Chapter 6 during the Implementation phase, further enhances the user experience by offering practical solutions to contemporary health inquiries. Harnessing the power of artificial intelligence, as detailed in Chapter 6, the Android-based Diet Consultant application empowers users to seize control of their health and contribute to a healthier, more informed future. As we delve deeper into the chapters, we will explore the meticulous methodologies and work plan, as presented in Chapter 3, the detailed system architecture design in Chapter 5, and the comprehensive testing and evaluation process in Chapter 7. Finally, in Chapter 8, we conclude by reflecting on the achievement of objectives, acknowledging limitations, and providing recommendations for future work.